"Dear Editor: Can You Tell Me What Happened to My Favorite NBC Program, Dimension X?". Issue 1 (2nd January 2019) - Keeler, Amanda
Abstract : Over the course of its seventeen-month run in 1950 and 1951, the science fiction anthology radio program Dimension X served as a showcase for many new and established science fiction writers. Dimension X was among several adult science fiction and fantasy shows that debuted on radio in the late 1940s and early 1950s, alongside CBS's Escape and Mutual's 2000 Plus. While many listeners celebrated these programs, NBC received letters detailing concerns over the subject matter of three episodes. In addition to providing insight into the reception of Dimension X, the responses from NBC personnel are equally informative. This back-and-forth communication provides a window into the network's efforts to mitigate and prevent listener issues, as well as the internal divisions regarding appropriate subject matter for radio programs in the early 1950s.